2021
DOI: 10.3390/pathogens10030344
|View full text |Cite
|
Sign up to set email alerts
|

Zur: Zinc-Sensing Transcriptional Regulator in a Diverse Set of Bacterial Species

Abstract: Zinc (Zn) is the quintessential d block metal, needed for survival in all living organisms. While Zn is an essential element, its excess is deleterious, therefore, maintenance of its intracellular concentrations is needed for survival. The living organisms, during the course of evolution, developed proteins that can track the limitation or excess of necessary metal ions, thus providing survival benefits under variable environmental conditions. Zinc uptake regulator (Zur) is a regulatory transcriptional factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 143 publications
(136 reference statements)
2
20
0
1
Order By: Relevance
“…As a result, the resistance of bacteria to antimicrobial substances and host immune response are improved ( Rahman and Karim, 2017 ). Furthermore, studies have shown that zinc promotes biofilm formation in P. aeruginosa and Xylella fastidiosa , which leads to difficulty in eradicating pathogens from the host ( Kumar et al, 2017 ; Kandari et al, 2021 ). Interestingly, Zn 2+ can also regulate transcription of RNA via regulation of the activity of transcription factors and several enzymes, such as RNA and DNA polymerases ( Nejdl et al, 2014 ).…”
Section: The Contribution Of Zinc To the Host–pathogen Interactionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, the resistance of bacteria to antimicrobial substances and host immune response are improved ( Rahman and Karim, 2017 ). Furthermore, studies have shown that zinc promotes biofilm formation in P. aeruginosa and Xylella fastidiosa , which leads to difficulty in eradicating pathogens from the host ( Kumar et al, 2017 ; Kandari et al, 2021 ). Interestingly, Zn 2+ can also regulate transcription of RNA via regulation of the activity of transcription factors and several enzymes, such as RNA and DNA polymerases ( Nejdl et al, 2014 ).…”
Section: The Contribution Of Zinc To the Host–pathogen Interactionmentioning
confidence: 99%
“…Extracellularly, members of the S100 protein family, such as calgranulin C, sequester zinc to inhibit microbial growth. In the face of these nutritional limitations, bacteria rely on an efficient zinc transport system to maintain zinc supplementation for proliferation and disruption of the host defense system to establish infection ( Figure 1 ; Schalk and Cunrath, 2016 ; Gonzalez et al, 2018 ; Cuajungco et al, 2021 ; Kandari et al, 2021 ).…”
Section: The Host Uses Nutritional Immunity To Limit the Acquisition Of Zinc By Pathogenic Bacteriamentioning
confidence: 99%
See 3 more Smart Citations